Control Strategy of Power Conversion System under Unbalanced Grid Voltage - Mingyong OU; Yichao WANG; Wenjun LIU; Xiangyang XIA; Lingbin CHEN; Yang LENG; Chuyu ZHENG (Zhongguo dianli, 2022)
Unbalanced grid voltage will cause voltage fluctuations on the DC side and active power fluctuations on the grid side, which seriously affects the safety and energy conversion efficiency of the energy storage battery system. Aiming at the above problems, this paper proposes a coordinated control strategy of DC side voltage and grid side active power. Firstly, by considering the active power fluctuation absorbed by the filter inductor on the AC side of the power conversion system, the suppression of the voltage fluctuation on the DC side is realized; Then, the weighted idea is used to coordinately control the voltage on the DC side and the active power on the grid side, and the fluctuation amplitude of the two is well reduced; Finally, the effectiveness and superiority of the proposed method are verified in the simulation.